Philippines : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Philippines. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2015)
This 2015 Article IV Consultation highlights that the Philippine economy continues to expand strongly in line with potential growth. Real GDP grew by 6.1 percent in 2014, driven by household consumption, private construction, and exports of goods and services. Economic growth slowed in the first quarter of 2015, owing mainly to temporary factors, including the effects of dry weather on agricultural production, weak global demand for exports, and slow budget execution. The outlook for the Philippine economy remains favorable despite uneven and generally weaker global growth prospects. Real GDP is projected to grow by 6.2 percent in 2015, as lower commodity prices lift household consumption and improved budget execution raises public spending.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet